Essa terra aqui é de Oxum, Xangô e Oxóssi : Um estudo sobre o candomblé na cidade de Goiânia - ULHOA, Clarissa Adjuto (2011)
Although it has been sustained for at least three decades a discourse obscuring the presence of candomblé in Goiânia, so far only been recognized the existence of umbanda, researchers reported not only for its presence in this city, but also a considerable number of terreiros that are currently in operation. Given this presence / absence of candomblé in Goiania, it is urgent to regional historiography to understand historical process of its installation, associated to the particular goianiense historical context and socio-cultural. Built in the thirties to meet the designs of the modern design of the new elites, this project which was ruled by a european model of modernity, the city of Goiânia, with its wide boulevards and its promises of progress, should act as the exact opposite of the old capital city of Goiás, where the alleys and colonial style houses revealed an unintended connection with the past, with what is understood as archaic. Therefore, this project of modernity upheld the official speeches of leaders, Catholic leaders, architects and planners, all directly involved in the consolidation of the aforementioned project. Historically considered by social agents of modernity as a mystical practice, candomblé would not have minimal chance to be included in cultural process of the government of the young capital, and consequently the inhabitants of the city idealized. This may have been one of the reasons that contributed to the later establishment of terreiro in the city, which occurred from the seventies, despite the massive migration from the Northeast, lured by promises of better life and whose cultural background was part of several african-brazilian religion elements. This particular context of the city of Goiânia has possibly contributed to showing how candomblé would be delineate there, besides the pressures by the opposition and christian religions, associated with police repression.